Web-based Business Reporting in Indian Corporate Sector - Verma, Divya (Journal of Knowledge Management Practice, 2010)
Internet has the widest reach as mode of communication in the present world of globalised economies. Recently the companies have started reporting their financial results and other information relating to business on their websites. Almost every company today maintains its website. It has been observed that information disclosed by companies on their websites largely depends on disclosure practices of competitors and industry standards. The present paper examines the disclosures of financial and non-financial information on websites by Indian companies. A sample of top 200 companies, which constitute BSE-200 Index, has been taken for the study. The sample comprises 19 diverse industry sectors. To measure the type and extent of web disclosure by the sample companies a worksheet referred as Internet Disclosure Index (IDI) has been prepared. The results summarized indicate that there is a positive relationship between industry sector to which a company belongs to and its internet reporting practices.